2016
DOI: 10.1007/s11904-016-0317-9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Sustained Retention in HIV/AIDS Care and Treatment: a Synthetic Review

Abstract: Sustained retention represents an enduring and evolving challenge to HIV treatment programs in Africa. We present a theoretical framework for sustained retention borrowing from ecologic principles of sustainability and dynamic adaptation. We posit that sustained retention from the patient perspective is dependent on three foundational principles: (1) patient activation: the acceptance, prioritization, literacy, and skills to manage a chronic disease condition, (2) social normalization: the engagement of a soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 63 publications
(52 reference statements)
1
16
0
1
Order By: Relevance
“…Roy et al suggest that sustained retention relies on patients’ ability to successfully integrate care and treatment activities with livelihood demands [41]. While this aspect of the framework is valuable, we also believe it is necessary to re-examine it through a gender lens.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Roy et al suggest that sustained retention relies on patients’ ability to successfully integrate care and treatment activities with livelihood demands [41]. While this aspect of the framework is valuable, we also believe it is necessary to re-examine it through a gender lens.…”
Section: Discussionmentioning
confidence: 97%
“…The framework posits that sustained retention is contingent upon 3 related processes: 1) patient activation, 2) social normalization and 3) livelihood routinization [41]. The process of patient activation involves a psychological shift from “passive recipients of care” to patients who accept their status, become more knowledgeable about their condition and engage with HCPs to co-manage their care.…”
Section: Discussionmentioning
confidence: 99%
“…To reach these targets, people living with HIV need to learn their HIV status, link to appropriate treatment, achieve virological suppression and remain in care and on treatment for their lifetime. Careful attention to each step along the treatment continuum is essential, 6 as sustained retention in care remains a challenge in many HIV programmes 7 …”
Section: Introductionmentioning
confidence: 99%
“…Social capital, and social support more broadly, has also been shown to positively impact HIV-related health at the individual and community levels (Gibbs, Campbell, Akintola, & Colvin, 2014;Wang & Eccles, 2012). Researchers have found that social capital, social network engagement, and forms of social support can support patient retention in HIV treatments (Roy et al, 2016), lead to greater quality of life for PLHIV (Jong, Carrico, Cooper, Thompson, & Portillo, 2017), and improve mental health outcomes for children living with HIV (Sharer, Cluver, Shields, & Ahearn, 2016). Alternatively, Cau, Falcao, and Arnaldo (2016) show that social isolation worsens health perceptions among urban adults in Mozambique.…”
Section: Social Protection To Improve Ovc Outcomesmentioning
confidence: 99%